2019
DOI: 10.22211/cejem/109742
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Insensitive RDX by Suspension Spray Technology and Its Characterization

Abstract: A new insensitive and high energy explosive based on RDX was prepared by suspension spray technology using Estane 5703 as a binder (e-RDX). Scanning electron microscopy was used to characterize the morphology and particle size of the samples. The composite was analyzed by differential scanning calorimetry and X-ray photoelectron spectroscopy. Its impact sensitivity and detonation velocity were determined. For comparison, raw RDX, refined RDX (r-RDX) and solution spray dried RDX/Estane 5703 (e1-RDX) were also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Philip Kneisl and Karri A. Brock modified the surface of RDX by recrystallization of RDX using two solvents to increase the sphericity of RDX crystals for reducing sensitivity [ 20 ]. Xiang Yan et al modified RDX by suspension spray technology using Estane 5703 as a binder [ 21 ]. Xue-Xue Zhang et al modified high explosives by crystallization for particle size and morphology tuning [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Philip Kneisl and Karri A. Brock modified the surface of RDX by recrystallization of RDX using two solvents to increase the sphericity of RDX crystals for reducing sensitivity [ 20 ]. Xiang Yan et al modified RDX by suspension spray technology using Estane 5703 as a binder [ 21 ]. Xue-Xue Zhang et al modified high explosives by crystallization for particle size and morphology tuning [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that, after refining particle size, the impact sensitivity is decreased, and the maximum detonation velocity is above 95% of the theoretical one. Yan et al [5] prepared a new insensitive and high energy explosive, based on RDX (e-RDX), by suspension spray technology, using…”
Section: Introductionmentioning
confidence: 99%
“…Common refining methods include anti‐solvent injection [5], spray drying [6–9], supercritical RESS [10–12], supercritical SAS [13, 14], and physical ball milling, among others. Coating methods include coating by water suspension [15–20], coating by a supercritical fluid [11, 21–28], coating by spray drying [29, 30], and coating by ball milling [31, 32]. The disadvantages of the two‐step process include high complexity, difficult process control, multi‐core capsules, irregular particle shapes, and uneven wall thickness.…”
Section: Introductionmentioning
confidence: 99%